Segmentation of quantity surveying professional services for focus strategy and diversification. Issue 3 (4th September 2019) - Adesi, Michael; Owusu-Manu, De-Graft; Boateng, Frank
Abstract : Purpose: Notwithstanding that numerous studies have focused on strategy in quantity surveying (QS) professional service firms, there is a paucity of investigation on the segmentation of QS professional services. The purpose of this study is to investigate the segmentation of QS services for diversification and a focus strategy formation. Design/methodology/approach: This study adopts the positivist stance and quantitative approach in which a simple random sampling technique was used to select participants. In total, 110 survey questionnaires were administered to registered professional QS, out of which 79 completed questionnaires were returned for analysis. Findings: The paper identifies three main QS service segments characterised by low, moderate and high competition. In addition, this study found that the concentration of traditional QS services in the building construction sector is due to the unwillingness of QS professional service firms to diversify into the non-construction sectors such as oil and gas. The diversification of QS services in the low competitive segment requires the adoption of agile approaches. Research limitations/implications: The study was limited to numeric analyses and so would be complemented by qualitative research in the future. Practical implications: This paper is useful to QS professional service firms interested in diversifying their services into the non-construction sectors to enhance the pricing of their services. Originality/value: Segmentation of QS services is fundamental to the formulation of focus strategy for non-construction sectors such as oil and gas and mining to enhance the pricing of QS professional services.